Practical use of the safety factor in the column repair strategy of a concrete building with historical value - Briceño Mena, Jorge Alberto; Castro Borges, Pedro (Revista ALCONPAT, 2022)
In this paper the practical use of the safety factor (FS) in the column repair strategy of a reinforced concrete building with historical value (almost 70 years) is presented. 80% of a building located in the historic center of the city of Campeche, Mexico, declared a World Heritage Site by UNESCO, was repaired. Strategies were used for a better use of material resources, equipment, and labor in the repair of walls, columns, slabs, and beams. One of the strategies was to use the theoretical FS to calculate the repair depth without structural consequences but fulfilling the purpose of controlling the carbonation of the concrete and maintaining the desired prediction of service life.